The effect of oil price on economic growth in lebanon: a markov-switching approach - AKGÜL, ŞEVKET IŞIL (My University, 2020)
This paper investigates the regime changes in the Lebanese economy using Markov Switching Auto Regressive models. Using the industrial production index and various variables, including oil prices, we identify two distinct regimes. The findings reveal that the Lebanese growth cycles are largely driven by seasonal effects and random shocks. The findings also indicate that the average duration of the instable and slow growth regime is much longer than that of the expansion and high growth regime. Finally, the probabilities of switching from one regime to another are rather very low but nearly zero for switching from the instable slow growth regime to the expansion and high growth regime. Hence, the estimated transition probabilities indicate the danger of the slowdown growth regime becoming permanent in Lebanon
Keywords: Crude oil price; Economic growth; Lebanon; MS-AR model